Influence of Regional Erosion and Sedimentary Loading on Fault Activities in Active Fold-Thrust Belts: Insights From Discrete Element Simulation and the Southern and Central Longmen Shan Fold-Thrust Belt - Wu, Zhenyun; Yin, Hongwei; Li, Changsheng; Yang, Xiulei; Wang, Li; Wang, Fuyuan; Dong, Shaochun; Jia, Dong (Frontiers in Earth Science, 2021)
Four groups of discrete element models (DEMs) were set-up to simulate and analyze the influence of regional erosion and sedimentary loading on the formation and spatial-temporal evolution of faults in the southern and central Longmen Shan (LMS) active fold-thrust belt. The interior characteristics of faults in the southern and central LMS fold-thrust belt were also evaluated during the interaction of tectonic processes and surface processes according to the stress-strain analysis from DEM results. The results showed that synkinematic erosion promoted the reactivation of pre-existing faults in thrust wedges and also retarded the formation and development of new incipient faults in the pre-wedge regions. Meanwhile, synkinematic sedimentation also delayed the development of new incipient faults in the pre-wedge regions by promoting the development of thrust faults in the front of thrust wedges, causing these thrust wedges in supercritical stages with relatively narrow wedge lengths. According to these DEM results, we infer that: 1) The characteristics of erosion and sedimentation in the central and southern LMS have important influences on the activities of large faults which are extended into the deep detachment layer; 2) Besides differential erosion, the differential sedimentary loading may also be one of the important factors for the along-strike differential evolution of the LMS fold-thrust belt. This kind of differential deposition may lead to differential fault activity and uplift in the interior thrust wedge and pre-wedge region in the central and southern LMS; 3) Compared to the northern LMS, the central LMS and southern LMS is more conducive to the occurrence of earthquakes, because of synkinematic sedimentation (such as the growth of Chengdu plain) has a greater blocking effect on the stress propagation and strain convergence on the fault planes of front faults of an active thrust wedge.